Laplace Adomian Decomposition and Modify Laplace Adomian Decomposition Methods for Solving Linear Volterra Integro-Fractional Differential Equations with Constant Multi-Time Retarded Delay (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this work, we present Laplace transform with series Adomian decomposition and modify Adomian decomposition methods for the first time to solve linear Volterra integro-differential equations of the fractional order in Caputo sense with constant multi-time Retarded delay. This method is primarily based on the elegant mixture of Laplace transform method, series expansion method and Adomian polynomial with modifications. The proposed technique will transform the multi-term delay integro-fractional differential equations into some iterative algebraic equations, and it is capable of reducing computational analytical works where the kernel of difference and simple degenerate types. Analytical examples are presented to illustrate the efficiency and accuracy of the proposed methods.